Corpse wore tartan - Dunnett, Kaitlyn (Thorndike, Me. : Center Point Large Print, 2010)
When Liss and the Scottish Heritage Appreciation Society get snowed in during a gathering for the Burns Night Supper, old grudges and whiskey heat up the atmosphere. Then a tartan-covered body is discovered in a storage room, and Liss helps her friends sort out the facts before more tempers--and lives--are lost.
"Cozy mystery"--P. [4] of cover.
" ... published in the year 2010 by arrangement with Kensington Publishing Corp."--T.p. verso.
100100
Keywords: Scottish Americans -- Maine; Women merchants -- Maine; Murder -- Investigation; Hotels; Large type books; Maine -- Social life and customs; Mystery fiction; Large type books